The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/sia.2787
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial studies of Al2O3 deposited on 4H‐SiC(0001)

Abstract: Al 2 O 3 films deposited on 4H-SiC(0001) by atomic layer deposition (ALD) were characterized by XPS, and high-resolution transmission electron microscopy (HRTEM). The effect of medium and high temperature (873, 1273 K) annealing on samples with oxide thicknesses of 5-8 and 100-120 nm was studied. XPS indicated the presence of a thin (∼1 nm) SiO x layer on the as-grown samples which increased to ∼3 nm after annealing above crystallization temperature (1273 K) in Ar atmosphere. Upon annealing the stoichiometry o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…On the other hand, in N 2 annealed samples at 300 °C show significantly higher peak of Si 0 and relatively lower peak of Si +1 oxidation state, referring to the un-oxidized Si. Whereas, very low quantity of Si +2 and Si +3 is present which could have been formed during the deposition process as indicated by Zhang et al [5] and Diplas [6]. The absence of Si +4 demonstrates that SiO 2 is not formed due to the presence of N 2 during the annealing.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, in N 2 annealed samples at 300 °C show significantly higher peak of Si 0 and relatively lower peak of Si +1 oxidation state, referring to the un-oxidized Si. Whereas, very low quantity of Si +2 and Si +3 is present which could have been formed during the deposition process as indicated by Zhang et al [5] and Diplas [6]. The absence of Si +4 demonstrates that SiO 2 is not formed due to the presence of N 2 during the annealing.…”
Section: Resultsmentioning
confidence: 95%
“…In recent years, the main focus in alternate dielectric search was on interface stability, easy process integration, and di electric constant value. The dielectrics investigated for this purpose are Al 2 O 3 [5][6][7], AlN [8], HfO 2 [9,10], Ta 2 O 5 [11], TiO 2 , etc and combinations of one or two dielectrics in layered form [9,14], as well as mixed form such as aluminum oxynitride (AlON) [15], Hf x Ti 1−x O 2 and Hf x Ti 1−x ON [13,16,17]. It is particularly important to note that most of the stacked and mixed dielectric efforts were made by adding thin SiO 2 as a first layer interfacing with 4H-SiC [18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the reduction of D it s is a consequence of interface modification upon high temperature treatment probably resulting in the formation of thin SiO 2 interfacial layer. 20 It has previously been shown that the high temperature treatment of Al 2 O 3 interface with SiC significantly improves the quality of the interface in terms of charges and interface states. Therefore, it can be concluded that high temperature treatment of Al 2 O 3 interface with SiC will improve the quality of the interface and does not degrade it.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, Al 2 O 3 deposited by atomic layer deposition (ALD) can only be used as a barrier in a very limited range of temper atures. Furthermore, several studies have shown that oxygen may react with SiC beneath Al 2 O 3 and form a thin layer of silicon oxide (SiO x , 1 ⩽ x ⩽ 2) at the interface [9][10][11].…”
Section: Introductionmentioning
confidence: 99%